Assessment of Dynamic Parameters of Rail Fastening - Jaroslav Smutny; Lubos Pazdera; Vladimir Tomandl; Herbert Seelmann (Communications - Scientific letters of the University of Zilina, 2016)
The paper is devoted to the analysis and comparison of the dynamic parameters of the rail fastening used in a standard way in the core railway network of the Czech Republic, i.e. the elastic rail fastening Vossloh W 14 and Pandrol FC. The paper also includes the description of the measurement and evaluation method. The conclusion of the paper is devoted to recommendations for further measurement and practical applications.